Taxation of sugar sweetened beverages and unhealthy foods: a qualitative study of key opinion leaders' views - Orly Tamir; Tamar Cohen-Yogev; Sharon Furman-Assaf; Ronit Endevelt (BMC, 2018)
Abstract Background Fiscal policies to fight obesity such as taxation of unhealthy foods or sugar-sweetened beverages (SSBs) have gained considerable attention in recent years. Many studies modelling the impact of various magnitudes of taxes on SSB purchasing and their potential effects on various health outcomes have been published; however, legislation and implementation of such taxes have encountered many obstacles in the countries that have implemented them to date. We investigated the perceptions and views of key opinion leaders, policy makers and various other Israeli stakeholders on taxation of SSBs and unhealthy snacks. We also evaluated the challenges and barriers that may be expected for initiating such a policy. Methods A qualitative study based on 39 in-depth interviews with Israeli stakeholders in the fields of health, nutrition, economics, public advocacy and policymaking. Results All stakeholders viewed obesity as a combined societal and personal issue that should be under government responsibility. Only stakeholders from economic sectors thought that taxation of SSBs and unhealthy snacks would reduce their consumption, while the prevailing notion among non-economists was that such a tax would not be acceptable because the higher price would not decrease consumption. Concerns were raised that the tax would mostly affect individuals from low socioeconomic backgrounds. Some of the stakeholders indicated that they would support such a tax only if its revenue would be directed to specific causes such as health-promoting plans. Potential barriers to taxation include: opposition of various sectors, technical and bureaucratic obstacles impeding tax implementation, difficulties in defining which products to tax, and opposition of the treasury to earmark tax revenue for health education. Conclusions Taxation should be a part of a multipronged strategy rather than a sole measure for fighting obesity. Dedicating tax revenues to specific predefined causes should be considered, particularly towards health promotion activities, obesity treatment and prevention, education, and subsidies of healthy food.